Perbedaan Frekuensi Konsumsi Fastfood Dan Aktivitas Fisik Antara Status Gizi Overweight Dan Non-Overweight Pada Siswa SMK Muhammadiyah 2 Surakarta - Putri, Leily Nurma, Eni Purwani, S.Si., M.Si, Isnaini Herawati, S.Fis, S.Pd, M.Sc (2016)
DEPARTEMENT OF NUTRITION SCIENCE FACULTY OF HEALTH SCIENCE UNIVERSITAS MUHAMMADIYAH SURAKARTA Introduction : Overweight happens when the weight is higher than the ideal weight which is caused by accumulation of fat and non fat tissues. The prevalence of overweight in Indonesia straight away increase, specially because of high fastfood consumption. Meanwhile, low physical activities constitute one of the causes of overweight. Purpose : To know the differences in frequency of fastfood consumption and phisical activities between overweight and non-overweight students at Muhammadiyah 2 vocational high school of Surakarta. Method : The research used cross-sectional design with 41 overweight subjects and 41 non-overweight subjects who were chosen by simple random sampling method. Frequency data on fastfood consumption were collected through FFQ form. Data on physical activities were obtained by recalling physical activities whereas nutritional status data were obtained by measuring height and weight. Result : Most subjects often consumed fastfood (68,3% in overweight and 63,4% in non-overweight subjects). Most subjects had light physical activity (65,9% in overweight and 61% in non-overweight). The differences in frequency of fastfood consumption and physical activity between overweight and non-overweight students showed p value 0,385 and 0,147 respectively. Conclusion : There were no differences in frequency of fastfood consumption and physical activities between overweight and non-overweight students at Muhammadiyah 2 vocational high school of Surakarta. Suggestion : Subjects need to reduce fastfood consumption and add physical activities while decreasing playing gadget. Key words : frequency fastfood consumption, physical activities, overweight, non-overweight. Litterature : 48 : 1994 - 2016